0436 Comparison of occupational physicians with attending physicians for opinions on collaboration with their counterparts. how to support of fitness for work of employees with diseases. (21st August 2017) - Muto, Go; Yokoyama, Kazuhito; Kitamura, Fumihiko; Endo, Motoki
Abstract : Objectives: To compare occupational physicians (OPs) with attending physicians (APs) for opinions on collaboration with their counterparts. Another purpose is to estimate the determinants of success of the collaboration. Methods: A questionnaire was mailed to both OPs belonging to the subcommittee of Japan Society for Occupational Health and APs belonging to Japan Medical Association. The questionnaire assessed demographics, opinions regarding collaboration such as medical information exchange with their counterparts, and successful or failed cases of cooperation. Results: A total of 94 OPs and 150 APs responded. Each of them offered 212 and 222 collaboration cases, respectively. From the analysis of successful cases, both groups showed mental disorder had the highest necessity of collaboration although APs showed relatively lower percentage (37%) compared with that of OPs (52%). From the perspective of situation of collaboration, approximately 60% cases occupied return-to-work and 35% cases showed the prevention of diseases exacerbation, which was the similar tendencies on both groups. However, 95% cases on OPs groups started from OPs side although only 48% cases on APs groups started from OPs side. OPs may like to start collaboration with APs but are unwilling to respond to APs letters. Furthermore, from the analysis of successful and failed cases of collaboration in mental disorders using chi-square test, the factors such as strong understanding of attending physicians (p=0.007) and superiors of the employees (p=0.041) for the collaboration, and controlled severity of diseases (p<0.001) were suggested to be significantly important in successful cooperative support for employees.